(untitled) (Fiep Bulletin - online, 2012)
Abstract: It is known that health care is gaining more prominence as regards the modalities of care to users of the public according to the level of complexity of the municipal health system. In this discussion deserves to be mentioned the work of Primary Health Care. The objective of the study is to know the attributes of primary care to provide quality care from the viewpoint of users. It is a cross-sectional study with a sample of 80 subjects treated in Primary Health Care in the city of João Pessoa / PB, in the year 2011. The results revealed that most respondents said they definitely seek a health service when it is disease and are treated in the same day. On the other hand, some weaknesses were perceived as difficult to get an appointment days in the month; delay in being seen at the clinic, see the user as a disease and not a human being, and not knowing what health problems are important for the user. Thus, one can conclude that there is need for review of community-based services in order to approximate the kind of careful, comprehensive, fair population in the provision of quality services, focusing on the points of weakness. It should also turn to the awareness of health professionals of the APS in order to attend to the proposed model of care and quality of health care.